ANÁLISE DE COMPONENTES PRINCIPAIS (ACP) NO COMPORTAMENTO DA EROSÃO HÍDRICA - MONTEIRO, Felipe Das Neves; FALCÃO, Karina Santos; FERREIRA, Rafael Silva; MENEZES, Roniedison da Silva; CRIVELLI, João Victor Souto; PANACHUKI, Elói (ANAIS DO ENIC, 2020)
-